The Effect of Eight Weeks of Selected Sensorimotor Exercises and Comprehensive Postural Reeducation on Lumbar Lordosis Angle and Postural Control in Women with Lower Crossed Syndrome - Miri , Hadi; Soltani , Mostafa; Nasri , Maryam (Health Nexus, 2025)
This study aimed to compare the effects of an eight-week program of selected sensorimotor exercises and a comprehensive postural reeducation protocol on lumbar lordosis angle and dynamic postural control in women with lower crossed syndrome. This applied, semi-experimental study employed a pretest–posttest design with two intervention groups and one control group. Thirty-six women aged 35–60 years diagnosed with lower crossed syndrome were recruited through purposive and convenience sampling and randomly assigned into three groups: sensorimotor training, comprehensive postural reeducation, and control. The interventions were conducted three times per week for eight weeks; each sensorimotor session lasted 40 minutes and focused on deep trunk activation and proprioceptive training, while postural reeducation sessions lasted 60 minutes and emphasized global myofascial stretching and sagittal alignment. Lumbar lordosis angle was measured using a flexible ruler, and dynamic postural control was assessed with the Star Excursion Balance Test (SEBT) for both dominant and non-dominant legs. Data were analyzed using analysis of covariance (ANCOVA) to compare post-intervention outcomes across groups. ANCOVA showed a significant group effect on lumbar lordosis angle (F = 22.45, p < 0.001, η² = 0.59), with both sensorimotor and postural reeducation groups achieving significant reductions compared to the control group, and postural reeducation outperforming sensorimotor training (mean difference = −2.01°, p = 0.032). For dynamic postural control, the sensorimotor group demonstrated significantly greater improvements than the control group in SEBT scores for both dominant (mean difference = 9.25%, p = 0.014) and non-dominant legs (mean difference = 12.47%, p = 0.008), while postural reeducation alone showed no significant advantage over control for balance outcomes. Both interventions improved spinal alignment in women with lower crossed syndrome, while sensorimotor training produced superior gains in functional balance.